A neglected homily by Caesarius of Arles. The complete version of Sermo Étaix 4 - Partoens, Gert (Revue d'études augustiniennes et patristiques, 2020)
In 1975, Raymond Étaix published a fragment of what he considered to be a lost sermon by Caesarius of Arles (sermon Étaix 4) based on the manuscript Paris, Bibliothèque nationale de France, Latin 2730. In the latter, this fragment (fol. 68v-69r) is attached as a kind of peroratio to a text which, according to Étaix, was Augustine’s sermon 304 on the martyr Laurentius (fol. 67r-68v). The present article argues, however, that the fragment is attached to a strongly modified version of the Augustinian homily and that the whole item on fol. 67r-69v is Caesarius’ sermon that Étaix supposed was lost. The article further suggests that, for the compilation of this homily, the Bishop of Arles used a more original version of Augustine’s sermon 304 than that which was transmitted by the sermon’s entire direct transmission and which can be found in modern editions. A critical edition of the new Caesarian sermon is given at the end of the article.